Essays on Finance and Risk - YIN, Shiyan (2024)
This thesis consists of three essays on corporate finance, with a focus on corporate governance in both the US and Chinese markets. The causal effect of reduced disclosure levels on the risk of default in the US market from 2008 to 2019 is examined in the first topic using regression discontinuity (RD) designs as the main identification strategy and the rule of Smaller Reporting Company Regulatory Relief and Simplification as the exogenous source of variation. The results indicate that smaller reporting companies, which are permitted to provide scaled disclosure in their 10-Ks, experience significantly and economically higher default risk. I demonstrate that the effect of information loss due to reduced disclosure levels dominates the effect of loss of commitment to mandatory disclosure and that, compared to previously qualified smaller reporting companies, newly qualified smaller reporting companies face steeper increases in bankruptcy risk during their first year of eligibility. The analyses also indicate that strong external oversight mechanisms, better corporate governance, and credible audit quality tend to alleviate the negative impact of reduced disclosure levels on the risk of default. The results are robust under alternative model specifications, regression discontinuity design assumptions and measures of default risk.